Incentives and Work Ability on Job Satisfaction through Performance - Kasrul Kasrul; Ali Murdhani Ngandoh (STIE Amkop Makassar, 2020)
This type of research used in this research is associative research. The research location is at PT. Surveyor Indonesia in the Pangkep Region. The sample in this study used the census method where the entire population was sampled in the study as many as 57 employees. In conducting statistical tests using path analysis. The results showed that incentives have a positive and significant effect on job satisfaction at PT. Surveyor Indonesia in the Pangkep Region. Job ability has a positive and significant effect on job satisfaction at PT. Surveyor Indonesia in the Pangkep Region. Incentives have a positive and significant effect on performance. Work ability has a positive and significant effect on performance. Job satisfaction has a positive and significant effect on performance. Incentives have a positive and significant effect on performance through job satisfaction. Job ability has a positive and significant effect on performance through job satisfaction at PT. Surveyor Indonesia in the Pangkep Region.